Evaluasi kesesuaian standar ukuran vertikal slot breket ortodonti The evaluation of the standard validity of vertical orthodontic bracket slot size - Parta L. Silitonga; Bergman Thahar; Endah Mardiati; Tono Hambali; Eky Soeria Soemantri (DiscoverSys Inc., 2013)
On orthodontic treatment, accuracy of orthodontic brackets slot size is essential for maximum interaction between thewire and brackets, so as to distribute the optimal force for tooth movement. The purpose of this study was to determinethe accuracy of orthodontic brackets slot size to 0.018 inch standard sizes that are available in the market. The samplewas selected by using a random sampling system, which consists of 15 types of brackets of 8 bracket manufacturerswith a total sample of 300 samples. Measurements performed on 4 sides of slot bracket, namely the outer and innersides of the brackets slot, on mesial and distal sides, using a profile projector (Mitutoyo Type PJ250). The results werestatistically tested using t-test one side. All brackets have a slot size significantly larger than the standard size. Theaverage percentage of magnification ranged from 5.18-24.29%. So, it was concluded that the size of the slot bracketsavailable in the Indonesian market greater than their standard.